2009
DOI: 10.1128/jvi.00352-09
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Changes in the Brains of Cattle Orally Infected with the Bovine Spongiform Encephalopathy Agent Precede Detection of Infectivity

Abstract: Bovine spongiform encephalopathy (BSE) is a fatal, transmissible, neurodegenerative disease of cattle. BSE can be transmitted experimentally between cattle through the oral route, and in this study, brain tissue samples from animals at different time points postinoculation were analyzed for changes in gene expression. The aims of this study were to identify differentially regulated genes during the progression of BSE using microarray-based gene expression profiling and to understand the effect of prion pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
5
28
0
1
Order By: Relevance
“…Although the brain tissues are severely damaged pathologically, the expression levels of prion protein gene PRNP do not differ distinctly compared with those of normal control, which is in accordance not only with the data of PRNP transcription in this patient with qRT-PCR, but also with the previous microarray findings in the sCJD patients (6), mice infected with scrapie or CJD agents (14) and cattle infected with the BSE agent (15). Maintenance of active transcription of the PRNP gene in CNS tissues at the terminal stage of human and animal prion diseases may indicate a special environment that facilitates the replication of prion agents locally by supplying enough PrP C as the substrates for PrP Sc replication.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the brain tissues are severely damaged pathologically, the expression levels of prion protein gene PRNP do not differ distinctly compared with those of normal control, which is in accordance not only with the data of PRNP transcription in this patient with qRT-PCR, but also with the previous microarray findings in the sCJD patients (6), mice infected with scrapie or CJD agents (14) and cattle infected with the BSE agent (15). Maintenance of active transcription of the PRNP gene in CNS tissues at the terminal stage of human and animal prion diseases may indicate a special environment that facilitates the replication of prion agents locally by supplying enough PrP C as the substrates for PrP Sc replication.…”
Section: Discussionsupporting
confidence: 77%
“…The most differentially expressed genes in G114V gCJD seem to be involved in multiple cell processes, such as regulation of transcription, ion transport, cell adhesion, signal transduction, nervous system development, oxidation reduction, protein transport, RNA splicing and synaptic transmission. In the brains of naturally-occurring or experimental animal and human TSEs, as well as in some prion infected cell lines (5,6,(15)(16)(17), abnormal alterations in ion transportation, transcription, cell adhesion, signal transduction and synaptic transmission have been repeatedly observed. Numerous differentially expressed genes involved in different cell processes or networks in brain tissues of this G114V gCJD patient reflect an extensive brain dysfunction at the final period of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tang et al (2009) identified 114 DE genes in brains of orally infected cattle vs uninfected controls and 10 DE genes identified by the authors were in common with our analysis. These genes may be an important key in pathogenic processes and need to be better investigated in animals with different genotypes, ages, doses of BSE infection and environment.…”
Section: Microarray Analysis Of De Genes Between Control and Bse-infesupporting
confidence: 61%
“…The common genes detected between our analysis and Tang et al (2009) were: S100 calcium binding and Calmodulin (up-regulated in both studies); Prolactin-related protein (downregulated in both studies); GTPase, IMAP family member, Histocompatibility complex, class II, Metallopeptidase (variable gene expression levels in the first study and up-regulated in our analyses) and Myosin, Glutathione S transferase A, Aldo-Keto reductase family and Nuclear receptor subfamily group H (down-regulated in the first study and up-regulated in our analysis). Notwithstanding these 10 genes that are in common between the studies, many genes identified were specific to one or the other study, which most likely is because different brain regions were used in the two studies: medulla was used in the present study while brain stem was examined by Tang et al (2009). Other factors that may have influenced the difference in results include the variation in the genetic composition of the animals; different microarray platforms and experimental conditions.…”
Section: Microarray Analysis Of De Genes Between Control and Bse-infementioning
confidence: 99%
“…Third, variations between individual animals may cause the different responses to BSE development. In the present study, data were only available for a single animal for each time point, and therefore Tang et al (2009), in which the largest numbers of differentially regulated genes were identified for 21 mo post infection brain as compared to the number of DE detected in the brain at 45 month post infection, supporting their speculation that global changes of gene expression activities are prior to the PrP BSE accumulation and the appearance of clinical signs. Findings of the large amount of DE gene at a preclinical stage suggest that these differences reflect probably a more specific prion-induced cellular response than those observed at the terminal stage of the disease when cells are seriously damaged.…”
Section: Microarray Analysis Of De Genes Between Control and Bse-infementioning
confidence: 79%